Ambivalensi Ketokohan Pangemanann dan Metafora “Rumah-Kaca”: Kajian Rumah Kaca, Karya Pramoedya Ananta Toer: The Ambivalence of Pangemanann's Character and the "Rumah-Kaca" Metaphor: A Study of the Rumah-Kaca, a Work by Pramoedya Ananta Toer - Gabriel Fajar Sasmita Aji; Kristophorus Budiman (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
This research examines two prominent elements: the ambivalence of Pangemanann's character and the metaphor of the "glass house." Criticism of colonization and authoritarian power is the strength of the novel Rumah Kaca. The strict surveillance system with the "glass house" model places the character Jacques Pangemanann as a colonial "puppet" to silence the colonized group. As a result, Minke, the postcolonialist, is killed, but behind this has emerged the meaning of postcoloniality that has gained a new form or perspective. Through a historical and postcolonial literary approach, this research presents memories of Indonesia's colonial history. It interprets the new model of Indonesian postcoloniality, shaped by the authoritarian strategy and the ambivalence of Pangemanann, a native who works for the colonial side. Rumah Kaca presents a historical narrative through the conflict between Pangemanann, who represents the colonial government, and Minke, a native of the colonized nation. Pangemanann's ambivalence stems from his being both the subject and the object of surveillance. The metaphor of a "glass house" alludes to the conditions of a colonized society that is strictly monitored by the state. The impact of this strict surveillance is the emergence of fear among the community and the death of Minke. The ambivalence of Pangemanann's character creates a new meaning in Indonesian postcoloniality. A new perspective emerges: postcoloniality is not about "who" but rather about "what" is carried. This meaning is emphasized through the metaphor of a "glass house." This metaphor refers to the condition of a colonized society, afraid because it is under surveillance by the colonial government. Moreover, this condition is actually carried out by a colonial agent, who is a native.